Island Development Authority Ninth Meeting (January 22 1996, New Delhi) - Planning Commission (Planning Commission Government of India, 1996)
The Ninth Meeting of the Island Development Authority, held on January 22, 1996, in New Delhi, focused on the strategic development of the Andaman & Nicobar Islands and Lakshadweep. Chaired by the Deputy Chairman of the Planning Commission, the meeting reviewed previous actions, addressed current challenges, and planned future initiatives for sustainable island development. Key discussions included enhancing local governance through legislative measures, extending financial powers of the Lt. Governor, regularizing ad-hoc employees, and improving educational access for island students. Development projects emphasized airport infrastructure, tourism promotion in Great Nicobar, and support for small scale industries, alongside careful environmental management of critical projects such as the Kalpong Dam. The meeting underscored a balanced approach to socio-economic growth while preserving ecological integrity, aiming to overcome geographic isolation and strengthen overall development in the island territories.
Planning Commission New Delhi
Keywords: Island Development Authority; Andaman & Nicobar Islands; Lakshadweep; Governance; Infrastructure; Tourism Development; Small Scale Industries; Environmental Management; Financial Empowerment; Educational Initiatives; Legislative Developments; Sustainable Development